2002
DOI: 10.1677/joe.0.1750417
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to pituitary surface antigens during various pituitary disease states

Abstract: Autoantibodies to cell surface antigens of human somatotropinoma (ASAS), human prolactinoma (ASAP) and rat adenohypophysis (ASARA) were assayed in the serum of patients with pituitary diseases associated with GH deficiency (GHD), such as pituitary dwarfism and primary empty sella syndrome (ESS), and in the serum of patients with hyperprolactinaemia of different etiologies: idiopathic hyperprolactinaemia, prolactinoma and ESS. The investigation was carried out with a cellular variant of an ELISA. Among children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…In particular, Beressi and colleagues concluded their excellent review by writing "empty sella may in fact be the final term of initially undiagnosed lymphocytic hypophysitis". Pituitary antibodies have been found in patients with empty sella ( [27]; Mau found by IB antibodies against human GH and ACTH in 2 of 6 patients (33%) [28]; and Keda by ELISA found them in 16 of 38 patients (42%) [22]. On the other hand, Bensing and colleagues found no evidence of autoimmunity in patients with empty sella: antibodies to 49 kDa alpha-enolase were present in 6 of 30 patients (20%), similar to what found in healthy controls (11 of 50, 22%) [29].…”
Section: Pituitary Antibodies In Non-autoimmune Pituitary Diseasesmentioning
confidence: 99%
“…In particular, Beressi and colleagues concluded their excellent review by writing "empty sella may in fact be the final term of initially undiagnosed lymphocytic hypophysitis". Pituitary antibodies have been found in patients with empty sella ( [27]; Mau found by IB antibodies against human GH and ACTH in 2 of 6 patients (33%) [28]; and Keda by ELISA found them in 16 of 38 patients (42%) [22]. On the other hand, Bensing and colleagues found no evidence of autoimmunity in patients with empty sella: antibodies to 49 kDa alpha-enolase were present in 6 of 30 patients (20%), similar to what found in healthy controls (11 of 50, 22%) [29].…”
Section: Pituitary Antibodies In Non-autoimmune Pituitary Diseasesmentioning
confidence: 99%
“…Moreover, some patients with idiopathic hyperprolactinemia could have a probable silent LYH. In fact, Keda et al showed recently that autoantibodies to surface antigens of prolactin-secreting cells are revealed significantly more frequently in patients with idiopathic hyperprolactinemia than in cases of hyperprolactinemia due to adenoma [48]. This suggests that also the evaluation of APA in patients with apparently idiopathic hyperprolactinemia and inconclusive MRI could be useful to disclose cases of subclinical LYH.…”
Section: Hyperprolactinemia In Lyhmentioning
confidence: 99%
“…Keda et al . showed that autoantibodies to surface antigens of PRL‐secreting cells are more frequently present in patients with idiopathic hyperprolactinemia than in cases of hyperprolactinemia due to adenoma 6 …”
Section: Introductionmentioning
confidence: 99%